Influence of Deflector Using on The Performance of Modified Savonius Water Turbine Vertical Axes - Sunarya, Franciskus Delaphius (SENATIK STT Adisutjipto, 2019)
Savonius turbine is a simple vertical axis turbine which work because of a difference drag force between blades. This turbine can convert kinetic energy on water flow into mechanical energy. The Savonius water turbine can work on low water flow speed. This research aimed at a Savonius turbine that has some of its parameters modified. The research tested the effects of water flow speed and the use of a deflector towards the modified Savonius turbine?s performance. It is concluded that Savonius turbine without the deflector, reached a maximum power coefficient at the flow speed of 1,1 m/s with the value of 0,163 at tip speed ratio of 0,845. As for the same speed (1,1 m/s) the turbine that used the deflector reached a maximum power coefficient of 0,307 at tip speed ratio 1,136. The highest coefficient of power was reached when the turbine got tested with the deflector at flow speed of 0,9 m/s with value of 0,354 at tip speed ratio 1,230.